Critical national response in coping with Omicron variant in China, Israel, South Africa, and the United States - Jun Jiao; Leiyu Shi; Haiqian Chen; Xiaohan Wang; Manfei Yang; Junyan Yang; Meiheng Liu; Gang Sun; Gang Sun (Frontiers Media S.A., 2023)
ObjectiveThe aim of this study was to analyze the effectiveness of prevention and control strategies and put forward further measures according to the epidemiological characteristics of Omicron. It summarized the national response during the Omicron epidemic in four countries: China, Israel, South Africa, and the United States.MethodsThis study summarized prevention and control measures in China, Israel, South Africa, and the United States in their response to the Omicron epidemic, and it also evaluated the effectiveness of these measures.ResultsAfter the Omicron variant emerged, China and Israel adopted containment strategies, using the "dynamic zero" policy and country closure measures. Meanwhile, South Africa and the United States adopted mitigation strategies, which virtually abandoned social interventions and only focused on medical measures and vaccines. From the first day of reported Omicron cases to 28 February 2022, the four countries reported the following cases: China reported 9,670 new confirmed cases and no deaths, with total deaths per million of 3.21; Israel reported 2,293,415 new confirmed cases and 2,016 deaths, with total deaths per million of 1,097.21; South Africa reported 731,384 new confirmed cases and 9,509 deaths, with total deaths per million reaching 1,655.708; the United States reported 3,042,743 new confirmed cases and 1,688,851 deaths, with total deaths per million reaching 2,855.052, which was much higher than the other countries.ConclusionBased on this study, it seems that China and Israel adopted containment strategies, while South Africa and the United States adopted mitigation strategies. A rapid response is a powerful weapon against the Omicron epidemic. Vaccines alone will not get any country out of this crisis, and non-pharmacological measures should be used in addition to them. According to the SPO model, future work should consider the strengthening of emergency management capacity, adhering to public health measures, promoting vaccination, and strengthening patient care and close contact management, which are effective measures in coping with Omicron.